(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Aim: The aim of the study is to estimate the high availability of stateful applications using novel kubernetes based microservice architecture over cloud based azure virtualization architecture. Materials and Methods: Sample groups that are considered in the project can be classified into two each has 20 samples, one for Microservice architecture and other for Virtualization architecture, which are tested using 0.80 for G-power to determine the sample size and for t-test analysis. 20 stateful applications have been used in each group for estimating high availability. Results: The novel kubernetes based microservice architecture with efficient accuracy of 90.20%,which by far seems to be better than the cloud based azure virtualization architecture which gives around 88.20%. The significance is around 0.329 (p>0.05) and therefore there is a statistical insignificant difference among the study group. Conclusion: Novel Kubernetes based microservice architecture seems to be better for stateful applications over the cloud based azure virtualization architecture.